Preventable Repeat Wrist Arthroscopies: Analysis of the Indications for 133 Cases - Löw, Steffen; Spies, Christian K.; Unglaub, Frank; van Schoonhoven, Jörg; Prommersberger, Karl-Josef; Mühldorfer-Fodor, Marion (Journal of Wrist Surgery, 2017)
Background Frequently, patients undergo repeated wrist arthroscopies for single wrist problems.Purpose The purposes of this study were to assess the indications for repeat wrist arthroscopies and to identify potentially preventable procedures.Methods For this retrospective, two-center study, the electronic patient records were examined for patients, who underwent repeat wrist arthroscopy in a 5-year period. The cases were sorted by the underlying pathologies and the causes that necessitated repeat arthroscopies.Results Ulnar-sided wrist pain accounted for 100 (77%) of all 133 revision arthroscopies: 67 of which due to suspected ulnar triangular fibrocartilage complex (TFCC) avulsions, 33 due to ulnar impaction syndromes. Cartilage was reassessed in 22 (17%) wrists. Thereby, insufficient preoperative diagnostics necessitated pure diagnostic before therapeutic arthroscopy in 49 (37%) wrists: 48 of which for TFCC pathologies, one for a scapholunate (SL) ligament lesion. The uncertainty of diagnosis despite previous arthroscopy necessitated 18 (14%) revision arthroscopies: 15 for ulnar TFCC avulsions, 1 for a central TFCC lesion, 2 to reevaluate the SL ligament. Inadequate photo or video documentation of the cartilage necessitated arthroscopic reassessment in 16 (12%) wrists.Conclusion In this series, two out of three revision arthroscopies could potentially have been prevented. Inadequate preoperative diagnostics with the lack of reliable preoperative diagnoses necessitated pure diagnostic arthroscopies for ulnar-sided wrist pain. However, even arthroscopically, the diagnosis of ulnar TFCC avulsions or SL ligament lesions is not trivial. Surgical skills and experience are necessary to detect such lesions. Finally, adequate photo or video documentation may prevent repeated arthroscopic diagnostic procedures.Level of Evidence Level IV.
Keywords: cartilage lesions; chondromalacia; photo and video documentation; scapholunate ligament; triangular fibrocartilage complex; revision wrist arthroscopy